Incidental Cone Beam CT Finding of Juvenile Pleomorphic Adenoma - Noura Alsufyani (Hindawi Limited, 2020)
Pleomorphic adenoma is a benign mixed tumor composed of epithelial and myoepithelial cells, less commonly occurring in minor salivary glands or in children. A case of juvenile pleomorphic adenoma missed clinically and incidentally found in cone beam CT images is described. Clinical, radiographic, and histologic images are presented.